Tissular distribution of argentinean strains of bovine herpesvirus type 4 (BoHV-4) in experimentally-infected calves - Morán, Pedro Edgardo (2017)
Although bovine herpesvirus type 4 (BoHV-4) is primarily associated with reproductive disorders of cattle, it can produce a variety of clinical signs. To determine the distribution, the presence and type of microscopic lesions caused by BoHV-4 strains of different genotypes an in vivo model, calves were infected with three phylogenetically different Argentinean BoHV-4 strains. Samples from nasal and ocular secretions, peripheral blood leukocytes, tissues and serum were analyzed. BoHV-4 was isolated from nasal and ocular secretions at 7 and 14 days post-inoculation (dpi). Viral DNA was detected by nested PCR in peripheral blood leukocytes at 14 and 21 dpi for two out of three strains and in tissues, such as nervous system, trachea, pulmonary and retropharyngeal lymph nodes, spleen and kidney, at 21 dpi. Antibody levels detected by viral seroneutralization test were mostly low and varied widely for the different strains. The tissue distribution of the BoHV-4 strains and the variations observed in the levels of neutralizing antibodies indicate that certain differences can be established among the patterns of biological behavior of each strain. This is an initial step to get insight into the biological characteristics of Argentinean BoHV-4 isolates. However, further evaluation involving a higher number of inoculated animals will be required to be conclusive on this aspect.